A mixed methods study on continuity and care coordination based on the obstetric near miss approach - Samuel M. Mulongo; Doreen Kaura; Bob Mash (AOSIS, 2024)
Background: The near-miss approach assumes that mothers facing life-threatening conditions such as severe pre-eclampsia and postpartum haemorrhage share common risk factors. Among these women, those who survive (near-miss cases) can offer insights into the determinants, providing valuable lessons for understanding underlying factors. Aim: To investigate elements of continuity and coordination leading to obstetric near misses. Setting: A major referral hospital and its referral pathway in Kenya. Methods: Explanatory sequential mixed-methods design. Results: Near-miss survivors had lower continuity and coordination of care indices during antenatal visits (COCI = 0.80, p = 0.0026), (modified continuity of care index [MCCI] = 0.62, p = 0.034), and those with non-life-threatening morbidity in the first trimester were more likely to experience a near miss (aOR = 4.34, p = 0.001). Facilities in the western region had a higher burden of near misses compared to the Eastern region. Qualitatively, three deductive themes were identified: sequential coordination, parallel coordination and continuity, along with factors classified as access. In mixed integration, poor continuity indices were explained by quality of interpersonal relationships and woman centredness. Poor coordination was explained by inadequate teamwork between providers in referring and referral facilities and between primary health facilities and the community. Higher near-miss rates in the western region resulted from differences in human and physical resources. Conclusion: Promoting woman-centred care, teamwork, improving communication and introducing innovative coordination roles like case and care managers can enhance continuity and coordination of maternal healthcare. Contributions: This study contributes to our understanding of the challenges of continuity and coordination in maternal healthcare in resource-poor settings by applying the WHO operationalisation of continuity and coordination using mixed methodology.